Costs and treatment patterns of incident ADHD patients: A comparative analysis before and after the initial diagnosis - Mike Klora; Jan Zeidler; Roland Linder; Frank Verheyen; Johann-Matthias Graf von der Schulenburg (Health Economics Review, 2015)
Background and objectives: The costs and treatment patterns of attention deficit hyperactivity disorder (ADHD) are subjects of health services research in Germany and worldwide. Previous publications focused mainly on prevalent patients and thus research gaps were identified regarding costs and treatment patterns of incident patients before and after the first diagnosis. Methods: Analyses were conducted using claims data obtained from a large German sickness fund (Techniker Krankenkasse). Inclusion criteria consisted of patients with at least two secured outpatient or one inpatient ADHD diagnosis in 2007. Incidence was ensured by defining a baseline period without ADHD-diagnosis in 2006. In addition to diseaserelated cost analyses compared to a control group including age group comparisons, comorbidities, the proportion of multimodal treatment and medication treatment patterns were described. Results: In total, 9083 newly diagnosed ADHD patients were identified (73 % male; mean age: 12.9 years (SD: 10.3)). The mean total cost of ADHD patients during the year after the first diagnosis exceeded the mean total cost of the year before by 976 exteuro Differencein-Difference-estimator: 1006 exteuro). Our analyses have shown that 10 % of ADHD patients have been treated with multimodal therapy. In addition, 11 % of the investigated ADHD population have received methylphenidate or atomoxetine preceeding the date of diagnosis in the relevant observation period. Discussion: This study provides important insights into the costs as well as the treatment patterns of incident ADHD patients. ADHD-related costs and medications can be identified prior to the date of the first ADHD diagnosis. Although, multimodal therapy is presented as an optimal treatment option by many international guidelines and experts, its proportion for treatment is low (10 %). Further research is necessary to identify reasons for the low proportion of multimodal therapy and (cost-)effectiveness has to be evaluated in comparison to other treatment options. In addition, ADHD-related costs could be identified before the first diagnosis is documented. The reasons for medication prior to diagnosis have to be further investigated.
Keywords: 330; Claims data; Incidence; ADHD; Costs; Germany